On approximation of the heat capacity of substances in the gaseous state - Belov, G. V.; Aristova, N. M.; Morozov, I. V.; Sineva, M. A. (Journal of mathematical chemistry, 2017)
Development of thermodynamic property databases and thermodynamic modeling algorithms require thermodynamic functions of substances presented in a functional form. In this paper we consider substances in the gaseous state only. The most known methods for approximating dependences of the thermodynamic functions on temperature are overviewed. An algorithm is proposed to fit the heat capacity with polynomials splitting the temperature range into intervals where the interval number and boundaries are optimized with respect to a given maximum approximation error. This algorithm is used in the IVTANTHERMO project and the corresponding thermodynamic modeling code.